Heart mitochondrial dysfunction in diabetic rats - Bombicino, Silvina Sonia (2016)
Diabetic cardiomyopathy, i.e. the ventricular dysfunction in the absence of hypertension or coronary arterial disease, is a common complication of diabetes mellitus that leads to a heightened risk of heart failure and death among diabetic patients. This contractile dysfunction could be associated to mitochondrial dysfunction, in which mitochondrial biogenesis could emerge as a compensatory mechanism triggered in response to hyperglycemia. It has been proposed that nitric oxide synthase activities with enhanced NO production are involved in this process. In streptozotocin-induced diabetic rats, alterations in contractile response and lusitropic reserve, after β adrenergic stimuli, were observed. Additionally, tissue O2 consumption was declined. A condition of mitochondrial dysfunction with decreased mitochondrial state 3 O2 consumption, respiratory control ratio, mitochondrial respiratory complexes activities and ATP production were present in hearts of diabetic animals. We observed an increase in mitochondrial NO production and in cytochrome oxidase activity measured in heart homogenates. This latter suggests an increase of new mitochondria. Thus, the impairment of mitochondrial function with enhancement in mitochondrial biogenesis could precede the onset of diabetic cardiomyopathy. However, mitochondrial biogenesis does not necessarily imply that resultant mitochondria are functional; this might explain the impairment in cardiac energy metabolism that occurs in hearts of diabetic rats.